PENGARUH PENGETAHUAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA PELAKU USAHA ONLINE - Gunarso, Pujo; Any Rustia Dewi, Any; Natasya Maheswari, Veronica (Jurnal GeoEkonomi, 2024)
The aim of this research is to determine the influence of tax knowledge and awareness on taxpayer compliance by online business actors. This research targets the field of taxation, specifically the influence of taxpayer knowledge and awareness on tax compliance by online business actors. The data used in this research is primary data obtained by distributing questionnaires to 60 respondents to the National Online Business in 2022. The sampling technique used simple random sampling. The data analysis technique used was multiple regression analysis using the SPSS version 25 program. The research results showed that tax knowledge had no effect on Taxpayer compliance with online economic business actors. Taxpayer awareness has a positive and significant effect on taxpayer compliance with online business actors. Keywords: Knowledge, Taxpayer Awareness, Online Business Taxpayer Compliance